Changing the release kinetics of gentamicin from poly(D, L-lactide) implant coatings using only one polymer - Strobel, Catrin; Schmidmaier, Gerhard; Wildemann, Britt (The international journal of artificial organs, 2011)
Creating orthopedic implants that locally deliver drugs is an appealing approach to induce bone regeneration and prevent or treat infections. In this study, titanium K-wires were coated with poly(D, L-lactide) (PDLLA) solutions with different polymer/solvent/drug ratios to modify the release kinetics of the antibiotic gentamicin. The concentrations of PDLLA ranged from one-fold (100 mg/1.5 mL solvent, 1X) to four-fold (400 mg/1.5 mL solvent, 4X), where the higher concentrations led to the thickening of the drug-loaded coatings and an increase of total coating mass. Coated wires were incubated in PBS buffer at 37°C for up to 32 weeks, and the elution kinetics were analyzed at several time points. Different release profiles were observed: I) a burst release within the first hours for the coatings made out of lower concentrations of PDLLA with higher amounts of gentamicin and II) a sustained release of up to 14 weeks for the different coatings with higher polymer amounts with lower concentrations of gentamicin. Moreover, the amounts of remaining gentamicin on the wires after elution were dependent on the coating composition. Nearly complete gentamicin was released from the 1X PDLLA coatings and approximately one-third with respect to initial gentamicin remained in the 4X coatings. Based on these results, we garnered a better understanding of the parameters that influenced release kinetics in this simple system and described how to realize different release patterns by using only one polymer. Using this knowledge, tailored coated implants that can improve infection prophylaxis or stimulate bone healing may be designed.
Gesehen am 24.10.2022